Consumers' Consciousness of Halal Certified UMKM Snack Food Products in Bandung City - Winesti, Cucu; Ningsih, Caria (Gastronomy Tourism Journal, 2019)
This research was motivated by the majority of Muslim consumers in Bandung. This of course affects the demand and supply of halal food products. This is in line with the development of SME snacks that are increasingly rife. This study aims to determine the relationship of halal consumer awareness factors to halal SME certified snack products in Bandung. Five factors that have been tested are religious beliefs, the role of halal certification, exposure information, health reasons, and self-identity. This research uses quantitative methods and survey research uses a questionnaire as an instrument with 100 reapondents. The targeted population is consumers who have never consumed halal-certified SME snack products in Bandung. The sampling technique uses purposive sampling method. The results of this study are, partial factors that influence consumer awareness of halal-certified SME snack products in Bandung, there are five factors that have a significant influence on religious beliefs, the role of halal certification, exposure information, health reasons, and self-identity and simultaneously the fifth factors that influence consumer awareness of halal SME certified snack products in Bandung have a significant influence. The continuum view of the halal consumer awareness line is very high. It is expected for further research to test orthher factors that have not been examined in this study because of the influence of the studied variables by 58.7%, while the remaining 41.3% of company variables have not been examined in this study